Exploring plant volatile-mediated interactions between native and introduced plants and insects - Effah E; Svendsen L; Barrett DP; Clavijo McCormick A (Springer Nature Limited, 2022)
In invasion scenarios, native and introduced species co-occur creating new interactions and modifying existing ones. Many plant-plant and plant-insect interactions are mediated by volatile organic compounds (VOCs), however, these have seldom been studied in an invasion context. To fill this knowledge gap, we explored some interactions mediated by VOCs between native and introduced plants and insects in a New Zealand system. We investigated whether a native plant, Leptospermum scoparium (mānuka), changes its volatile profile when grown adjacent to two European introduced plants, Calluna vulgaris (heather) and Cytisus scoparius (Scotch broom), in a semi-field trial using potted plants without above- or below-ground physical contact. We also investigated the influence of plant cues on the host-searching behaviour of two beetles, the native Pyronota festiva (mānuka beetle), and the introduced biocontrol agent Lochmaea suturalis (heather beetle), by offering them their host-plant and non-host volatiles versus clean air, and their combination in a Y-tube olfactometer. As a follow-up, we performed preference/feeding tests in Petri dishes with fresh plant material. Results of the semi-field experiment show a significant reduction in green leaf volatiles, sesquiterpenes and total volatile emissions by mānuka plants neighbouring heather. In the Y-tube assays, the native beetle P. festiva performed poorly in discriminating between host and non-host plants based on plant volatile cues only. However, it performed relatively well in the Petri dish tests, where other cues (i.e., visual, gustatory or tactile) were present. In contrast, the introduced beetle L. suturalis showed high host-specificity in both Y-tube and Petri dish assays. This study illustrates the importance of VOCs in mediating interactions between introduced and native species, suggesting that invasive plants can disrupt native plants' communication and affect the host-searching behaviour of native insects. It also reinforces the relevance of regular host testing on introduced weed biocontrol agents to avoid unwanted host shifts or host-range expansion.
Keywords: Animals; Coleoptera; Cytisus; Introduced Species; Plants; Volatile Organic Compounds